Cardiovascular Magnetic Resonance–Guided Electrophysiological Interventions: Radiofrequency Ablation of Typical Atrial Flutter. (January 2017) - Paetsch, Ingo; Jahnke, Cosima; Hilbert, Sebastian; Krueger, Sascha; Weiss, Steffen; Smink, Jouke; Schnackenburg, Bernhard; Lloyd, Tom; Hindricks, Gerhard; Sommer, Philipp
Abstract : Supplemental Digital Content is available in the text.